2009
DOI: 10.1016/j.yhbeh.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Sexual differentiation of motivation: A novel mechanism?

Abstract: Sex differences in motivation are apparent for the motivation to engage in sexual behavior, the motivation to take drugs of abuse, and the motivation to engage in parental behavior. In both males and females there is an increase in NAcc DA associated with motivated behaviors. Here it proposed that sex differences in the regulation of DA activity in the ascending mesolimbic projections may underlie sex differences in motivation. In particular, sex differences in the neuroendocrine regulation of this brain syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 144 publications
1
94
0
6
Order By: Relevance
“…Here, we demonstrate that blockade of -opioid receptors (known to mediate aversion) (Mucha and Herz, 1985;Pfeiffer et al, 1986), but not -opioid receptors (known to mediate reward and positive hedonics) (Weeks, 1962;Bozarth and Wise, 1981), prevents selective aggression. These effects are specific to the NAc shell, a component of brain motivational circuitry that is critical for neural processing of both social bonding (Li and Fleming, 2003;Champagne et al, 2004;Aragona et al, 2006;Aragona and Wang, 2007) and unconditioned incentives, including those of an aversive nature (Kalivas and Duffy, 1995;Ikemoto and Panksepp, 1999;Kelley and Berridge, 2002;Everitt and Robbins, 2005;Becker, 2009). As such, the current data suggest that -opioid receptors within this region may facilitate the tagging of social stimuli as aversive and cause novel conspecifics to be aggressively rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that blockade of -opioid receptors (known to mediate aversion) (Mucha and Herz, 1985;Pfeiffer et al, 1986), but not -opioid receptors (known to mediate reward and positive hedonics) (Weeks, 1962;Bozarth and Wise, 1981), prevents selective aggression. These effects are specific to the NAc shell, a component of brain motivational circuitry that is critical for neural processing of both social bonding (Li and Fleming, 2003;Champagne et al, 2004;Aragona et al, 2006;Aragona and Wang, 2007) and unconditioned incentives, including those of an aversive nature (Kalivas and Duffy, 1995;Ikemoto and Panksepp, 1999;Kelley and Berridge, 2002;Everitt and Robbins, 2005;Becker, 2009). As such, the current data suggest that -opioid receptors within this region may facilitate the tagging of social stimuli as aversive and cause novel conspecifics to be aggressively rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Self-administration of drugs in experimental animals is used as a model of human addictive behavior, allowing separate analysis of the acquisition, maintenance, and motivation to seek reward. These data are excellently reviewed elsewhere (Lynch et al, 2002;Lynch, 2006;Becker and Hu, 2008;Becker, 2009), and the salient points are summarized here. Compared with males, female rats acquire cocaine self-administration and cocaine-induced conditioned place preference (a test to determine the rewarding effect of cocaine) faster and at a lower dose.…”
Section: B Preclinical Evidencementioning
confidence: 93%
“…The behavioral effects of the psychomotor stimulants therefore seem to be sexually dimorphic and sensitive to the prevailing hormonal environment. Convergent evidence suggests that the ventral striatum and amygdala respond to predictors of reward or anticipation (motivational behavior, or the appetitive component of a behavior), rather than the reward itself (the consummatory component of a behavior); the mesolimbic DA system and DA release in the nucleus accumbens play a particularly important role in the motivational and reward network, whereas medial prefrontal cortex and the dorsal striatum are more responsive at the time of reward (O'Doherty, 2004;Becker, 2009). Although relatively little is known about hormonal influences on the DA-reward system in humans, in vivo imaging studies have demonstrated fluctuations over the menstrual cycle (Caldú and Dreher, 2007) and sex differences in striatal DA release in healthy men and women (Munro et al, 2006).…”
Section: A Epidemiological and Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Female participants were given a urine pregnancy test before each PET session; none tested positive (Assure FastRead hCG Cassette, Conception Technologies, San Diego, California, USA). As gonadal hormone levels fluctuate during the menstrual cycle and these changes are thought to influence reward-related neurotransmission (Becker, 2009), female participants were tested during their follicular phase when estradiol and progesterone levels are lower and more stable. Menstrual phase was verified by self-report and all were tested in the first 7 days of their cycle.…”
Section: Methodsmentioning
confidence: 99%